(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
The issues of raising the physically healthy and spiritually mature young generation are one of the most topical issues of today. The study of some morphologically important physical development indicators of young school-age children, the study of health indicators is of great importance. This article provides a statistical analysis of some morphological indicators of primary school children of secondary school. Based on the results, appropriate suggestions and conclusions are made.